2015
DOI: 10.1063/1.4933086
|View full text |Cite
|
Sign up to set email alerts
|

Roles of individual radicals generated by a submerged dielectric barrier discharge plasma reactor during Escherichia coli O157:H7 inactivation

Abstract: A submerged dielectric barrier discharge plasma reactor (underwater DBD) has been used on Escherichia coli O157:H7 (ATCC 35150). Plasma treatment was carried out using clean dry air gas to investigate the individual effects of the radicals produced by underwater DBD on an E. coli O157:H7 suspension (8.0 log CFU/ml). E. coli O157:H7 was reduced by 6.0 log CFU/ml for 2 min of underwater DBD plasma treatment. Optical Emission Spectra (OES) shows that OH and NO (α, β) radicals, generated by underwater DBD along wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
21
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 51 publications
0
21
0
Order By: Relevance
“…In case of OH radical, it was observed that after 6–8 min of DBD operation, the intensity or concentration of 2-hydroxyterephthalic acid (HTA) or OH radical (1 mol of OH radical ≡ 1 mol of HTA) was decreased whereas the concentration of HTA (OH radical) was supposed to be either increased or remained constant. Decreasing phenomena of OH radical was described in detail with experimental evidence in the previous work10. Actually dissolved ozone, OH radical and H 2 O 2 concentration remains constant throughout the 90 min of plasma treatment after 4 min, 8 min and 6 min of plasma generation, respectively.…”
Section: Discussionmentioning
confidence: 59%
See 4 more Smart Citations
“…In case of OH radical, it was observed that after 6–8 min of DBD operation, the intensity or concentration of 2-hydroxyterephthalic acid (HTA) or OH radical (1 mol of OH radical ≡ 1 mol of HTA) was decreased whereas the concentration of HTA (OH radical) was supposed to be either increased or remained constant. Decreasing phenomena of OH radical was described in detail with experimental evidence in the previous work10. Actually dissolved ozone, OH radical and H 2 O 2 concentration remains constant throughout the 90 min of plasma treatment after 4 min, 8 min and 6 min of plasma generation, respectively.…”
Section: Discussionmentioning
confidence: 59%
“…Among these radicals, the OH radicals play a major role in inactivation, with dissolved O 3 gas ranking next in importance. H 2 O 2 was found to play no role in E. coli O157:H7 inactivation in our study because the amount of hydrogen peroxide produced during our treatment time was very low (2.5 × 10 −6  M) and remains constant throughout the operation10. The inactivation mechanism of E. coli O157:H7 via the OH radical may proceed through some chemical or physical process; OH radicals are considered to enhance chemical reactions and also have a damaging effect on the unsaturated fatty acid side chains of lipid bilayers in various cell membranes6263.…”
Section: Discussionmentioning
confidence: 60%
See 3 more Smart Citations